2018
DOI: 10.1371/journal.pone.0195317
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided lumbar puncture with a needle-guidance system: A prospective and controlled study to evaluate the learnability and feasibility of a newly developed approach

Abstract: ObjectiveTo evaluate the learnability and feasibility of a new technique comprising a needle-guidance-system (NGS) for ultrasound-assisted lumbar puncture.MethodUsing a randomized crossover study design, 24 medical students were asked to perform an ultrasound-assisted lumbar puncture on a gel phantom using two different techniques that each included a paramedian insertion site. Procedure 1 (P1) used a pre-procedural ultrasound scan to predetermine the ideal insertion point. Procedure 2 (P2) applied a new techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 38 publications
0
17
0
7
Order By: Relevance
“…The predicted trajectory and actual position of the needle are also shown in the ultrasound view. In previous studies, the electromagnetic guidance system resulted in favourable outcomes when performing ultrasound-guided procedures using the phantom model [ 11 13 ]. However, the clinical advantages of the electromagnetic guidance system have not been previously validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted trajectory and actual position of the needle are also shown in the ultrasound view. In previous studies, the electromagnetic guidance system resulted in favourable outcomes when performing ultrasound-guided procedures using the phantom model [ 11 13 ]. However, the clinical advantages of the electromagnetic guidance system have not been previously validated.…”
Section: Discussionmentioning
confidence: 99%
“…It also shows the expected route and tip of the needle. In several studies using a gel phantom model, the novel electromagnetic guidance system appears capable of reducing the incidence of complications and improving the success rate of invasive procedures among providers with or without sufficient experience with radial artery cannulation under ultrasound guidance [ 11 13 ]. However, no clinical in vivo studies have been conducted on the efficacy of the electromagnetic ultrasound guidance system during invasive procedures such as central venous catheterization or radial artery cannulation.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should further evaluate the potential for this type of intervention to contribute to improvements in procedural skills that may directly impact patient outcomes. Studies that consider how incorporating technological innovations (e.g., ultrasound guided lumbar puncture [22]) may expedite the achievement of behavioural fluency, and/or improve training outcomes, would be of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there was also a reduction in performance time (118 seconds vs. 80.6 seconds, respectively, P < .001), and 23 of 24 participants reported that they preferred the real-time, NGS-assisted LP. 86 Traditionally, physicians have learned to perform LP through unstructured observation and supervision during medical training.…”
Section: Emerging Techniques and Innovations In Lpmentioning
confidence: 99%